Ranunculaceae endémicas del Perú - León, Blanca (2006)
The Ranunculaceae are represented in Peru by eight genera and 50 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly herbs. Here we recognize eight endemic species in three genera. One genus, Laccopetalum, is endemic to Peru. Ranunculus is the genus with the largest number of endemic species. Endemic species are found mainly in Paramo, and Humid and Dry Puna regions, between 3200 and 4800 m elevation. We applied IUCN categories and criteria to six species. Apparently, four species have been recorded within Peru’s protected areas system.